2020
DOI: 10.3390/microorganisms8101573
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Yeast-Derived β-Glucans on the Porcine Gut Microbiota and Immune System in Early Life

Abstract: Piglets are susceptible to infections in early life and around weaning due to rapid environmental and dietary changes. A compelling target to improve pig health in early life is diet, as it constitutes a pivotal determinant of gut microbial colonization and maturation of the host’s immune system. In the present study, we investigated how supplementation of yeast-derived β-glucans affects the gut microbiota and immune function pre- and post-weaning, and how these complex systems develop over time. From day two … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
35
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(37 citation statements)
references
References 68 publications
2
35
0
Order By: Relevance
“…β-glucans have a direct effect on the human and animal immune system [ 1 ], and stimulate gut microbiota activity in the lower gastrointestinal tract. The effect on the gut microbiome has been observed mostly in vitro and in human [ 6 , 8 ] and pigs [ 7 , 9 ]. However, in our study, we observed no effect on bacterial diversity and structure.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…β-glucans have a direct effect on the human and animal immune system [ 1 ], and stimulate gut microbiota activity in the lower gastrointestinal tract. The effect on the gut microbiome has been observed mostly in vitro and in human [ 6 , 8 ] and pigs [ 7 , 9 ]. However, in our study, we observed no effect on bacterial diversity and structure.…”
Section: Discussionmentioning
confidence: 99%
“…Unlike probiotics, few studies have been conducted to understand the effects of prebiotics on ruminants [ 3 ]. However, in nonruminants and humans, the effects are beneficial, such as promoting higher bacterial richness, higher abundance of Bifidobacterium and Lactobacillus , immunomodulation, nutrient absorption effects, and an improved gut barrier [ 6 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…β-glucans have potent immunomodulatory properties [reviewed in (40)]. For example, they are able to alter the gut microbiota and immune system of pre-weaned piglets when supplemented to the feed (23). Furthermore, in-feed supplementation of β-glucans after weaning led to a reduced susceptibility to F4 + ETEC infection in vivo (41).…”
Section: Discussionmentioning
confidence: 99%
“…For example, a dose-dependent inhibition of human NK cell killing of different target cells by zymosan and a particulate yeast glucan was described (22). In pigs, an in vivo study suggested that oral delivery of yeast-derived β-glucans impacted on the number of proliferating NK cells (23). This might indicate that β-glucans also influence porcine NK cells.…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, yeast β-glucan preparations have been popularly promoted as daily nutritional and medicinal supplements in humans to enhance immunomodulatory function (Stier et al, 2014;Jayachandran et al, 2018;Wang et al, 2020b). Furthermore, as effective antibiotic alternatives, yeast β-glucan has been applied in poultry production for its beneficial growthpromoting, strong immune-regulating, anti-inflammatory, antiinfective, and immune adjuvant effects (Cox et al, 2010a;Stier et al, 2014;Vetvicka and Oliveira, 2014;Moon et al, 2016;de Vries et al, 2020). Recently, several studies identified the prebiotic properties and health-promoting benefits of yeast β-glucan, which are facilitated by modulating porcine and murine gut microbiota as well as regulating intestinal immune responses (Sweeney et al, 2012;Charlet et al, 2018;Gudi et al, 2019;de Vries et al, 2020;Wang et al, 2020a).…”
Section: Introductionmentioning
confidence: 99%